Some characteristics of dry-cured ham obtained from Sicilian Nero pig: comparison between two different ripening techniques - Diaferia C.; D' Amico A.; Madonia G.; Margiotta S.; Cartabellotta D.; Pruiti V. (5. International Symposium on the Mediterranean Pig, 2007)
In the countries of Mediterranean Europe there exists a long-standing tradition of pork products. However, the evolution of the breeding techniques and the use of genetic types capable of high productivity have considerably modified meat, pork meat products and ripening techniques. Recent experiments have reintroduced the original characteristics of these products through the revival of the local swine breed. The Region of Sicily has started a program for the enhancement of the Nero Siciliano pig, also through the development of some dried cured products, like the country ham. This experimental work has been carried out towards the rationalization of the processing techniques for the preparation of the dry-cured ham, through the comparison of two ripening techniques: traditional and conditioned. The results obtained are due for further investigation, as no significant differences have been shown between the two techniques, and have raised new perspectives for the enhancement of the local dry-cured ham.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)